2021
DOI: 10.1111/risa.13856
|View full text |Cite
|
Sign up to set email alerts
|

Judging Pharmaceutical Environmental Risk by its Cover? The Effects of Prescription Medication and Disease Severity on Environmental Risk Perception

Abstract: Recent wastewater analyses performed in care homes for the elderly showed high levels of water pollution resulting from pharmaceutical waste. The way people perceive the environmental risk of pharmaceuticals can contribute to reversing this problem, but the factors that influence risk perception remain relatively unknown. The aims of the study are two‐fold. We first focused on exploring the levels of knowledge regarding environment/water pollution due to pharmaceutical residues from the groups responsible for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 32 publications
(47 reference statements)
0
3
0
Order By: Relevance
“…In the medication waste field, we can define risk perception as assessing the risks associated with poor disposal practices of excess medications and knowing the negative consequences of those actions on both health and the environment. The previous literature revealed that medication waste contributes to environmental damage (such as water and air poisoning) which negatively affects living organisms and human health [ 19 , 21 ]. In some cases, the medication waste can cause air poisoning, which results in or exacerbates various respiratory diseases (asthma, chronic obstructive pulmonary disease, emphysema).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…In the medication waste field, we can define risk perception as assessing the risks associated with poor disposal practices of excess medications and knowing the negative consequences of those actions on both health and the environment. The previous literature revealed that medication waste contributes to environmental damage (such as water and air poisoning) which negatively affects living organisms and human health [ 19 , 21 ]. In some cases, the medication waste can cause air poisoning, which results in or exacerbates various respiratory diseases (asthma, chronic obstructive pulmonary disease, emphysema).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…); storage of unused medications; throwing medications in rubbish, latrines, and drains; as well as donating stored medications to relatives, friends, and neighbors [ 10 ]. Moreover, these behaviors are often associated with a lack of environmental awareness and knowledge about the negative consequences and effects of wasted medications [ 1 , 18 ] and lower levels of perceived risk associated with wasted medications [ 21 ]. In this context, Kahssay et al [ 5 ] found that 84.1% of the respondents in Ethiopia “had never heard/learned” about methods of safe disposal of medications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation